Socio-Economic Determinants of Obesity in Indonesia: Analysis of IFLS 2014 Data - Niko Sangaji; Vincent Hadi Wiyono; Tri Mulyaningsih (Budapest International Research and Critics University, 2022)
The phenomenon of obesity has become a serious problem in various countries, especially in Indonesia. According to WHO in 2016 there were 2.8 million people who died due to the problem of obesity, while according to the Indonesian Ministry of Health the prevalence of overweight and obesity in Indonesia in 2018 reached 13,6% and 21.8%. One of the factors that cause obesity is socio-economic status. However, there are often differences regarding the effect of socioeconomic status on obesity in developing and developed countries. This study aims to identify the determinant factors of socioeconomic status on overweight and obesity. The data used comes from the Indonesian Family Life Survey (IFLS) 5 in 2014 with samples are aged more than 18 years. The analysis was conducted by using the Ordered Logistic Regression model. The results of this study indicate that statistically, individuals with higher socioeconomic status have a higher chance of experience overweight and obesity. Therefore, the socialization of health care programs needs to be improved, especially in the community and schools to increase knowledge, awareness, and change lifestyles to be healthier.